Crosstalk among N6-methyladenosine modification and RNAs in central nervous system injuries - Tian, Mi; Mao, Lei; Zhang, Li (Frontiers in Cellular Neuroscience, 2022)
Central nervous system (CNS) injuries, including traumatic brain injury (TBI), intracerebral hemorrhage (ICH) and ischemic stroke, are the most common cause of death and disability around the world. As the most common modification on ribonucleic acids (RNAs), N6-methyladenosine (m6A) modification has recently attracted great attentions due to its functions in determining the fate of RNAs through changes in splicing, translation, degradation and stability. A large number of studies have suggested that m6A modification played an important role in brain development and involved in many neurological disorders, particularly in CNS injuries. It has been proposed that m6A modification could improve neurological impairment, inhibit apoptosis, suppress inflammation, reduce pyroptosis and attenuate ferroptosis in CNS injuries via different molecules including phosphatase and tensin homolog (PTEN), NLR family pyrin domain containing 3 (NLRP3), B-cell lymphoma 2 (Bcl-2), glutathione peroxidase 4 (GPX4) and long non-coding RNA (lncRNA). Therefore, m6A modification showed great promise as potential targets in CNS injuries. In this article, we present a review highlighting the role of m6A modification in CNS injuries. Hence, on the basis of these properties and effects, m6A modification may be developed as therapeutic agents for CNS injury patients.